The Relationship Between Secure Attachment of Parents and Children in Early Childhood - Dian Adinissa; Nono Hery Yoenanto; Suryanto Suryanto (International Journal Labs, 2025)
The bond between parents and children is an emotional bond, considering that a child is conceived for 9 months in his mother's womb until he is born into the world. The family certainly has an important role as the main shaping of a child's character, because the parenting of both fathers and mothers at home for children greatly affects the development that occurs in children. This research uses the Literature Review Technique or the technique of reviewing written works as a method of collecting literature data or research libraries or scientific papers. The primary data sources in this study are the results of research or scientific papers along with books related to the safe attachment relationship between parents and their children at an early age. The purpose of this research is to increase insight for parents as an effort to shape children's character, especially at an early age, especially in understanding the benefits of the secure attachment relationship that exists between parents and children. Studies from several previous studies related to safe attachment will be described descriptively in this study, such as explaining the factors that affect the safe attachment between parents and children and their positive impact on early childhood development so as to provide an overview of the safe attachment between parents and children.